(Not) Eating for the environment: The impact of restaurant menu design on vegetarian food choice. (1st June 2018) - Bacon, Linda; Krpan, Dario
Abstract: Previous research has shown that restaurant menu design can influence food choices. However, it remains unknown whether such contextual effects on food selection are dependent on people's past behavior. In the present study, we focused on vegetarian food choices, given their important implications for the environment, and investigated whether the influence of different restaurant menus on the likelihood of selecting a vegetarian dish is moderated by the number of days on which people reported eating only vegetarian food during the previous week. In an online scenario, participants were randomly assigned to four different restaurant menu conditions—control (all dishes presented in the same manner), recommendation (vegetarian dish presented as chef's recommendation), descriptive (more appealing description of vegetarian dish), and vegetarian (vegetarian dishes placed in a separate section)—and ordered a dish for dinner. The results showed that the recommendation and descriptive menus increased the likelihood of vegetarian dish choices for infrequent eaters of vegetarian foods, whereas these effects tended to reverse for those who ate vegetarian meals more often. The vegetarian menu had no impact on the infrequent vegetarian eaters' choice but backfired for the frequent vegetarian eaters and made them less likely to order a vegetarian dish. These findings indicate that people's past behavior is an important determinant of the impact of nudging on food choices, and that achieving sustainable eating may require more personalized interventions.